2001
DOI: 10.1007/s002340000470
|View full text |Cite
|
Sign up to set email alerts
|

Choroid plexus papilloma of the third ventricle: angiography, preoperative embolization, and histology

Abstract: We report a unique case of choroid plexus papilloma of the third ventricle in an 8-month-old girl in which preoperative embolization played a salient role in management. Initial surgery was aborted due to excessive bleeding. Cerebral angiography demonstrated enlarged posterior choroidal arteries feeding the tumor, and intense, persistent tumor staining. These vessels were effectively embolized to stasis with polyvinyl alcohol particles. The patient underwent a second craniotomy and complete resection of the tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 0 publications
0
31
0
Order By: Relevance
“…However, the catheterization of narrow arteries in infants is not always feasible, 7) as only 6 of 13 procedures were successful. 3,6,7,9) In the present case, the efficacy of the embolization was unclear because only one of the feeding arteries from the anterior choroidal artery was embolized. However, the second surgery was safely carried out without excessive bleeding.…”
Section: Discussionmentioning
confidence: 72%
“…However, the catheterization of narrow arteries in infants is not always feasible, 7) as only 6 of 13 procedures were successful. 3,6,7,9) In the present case, the efficacy of the embolization was unclear because only one of the feeding arteries from the anterior choroidal artery was embolized. However, the second surgery was safely carried out without excessive bleeding.…”
Section: Discussionmentioning
confidence: 72%
“…As the third ventricle is small and complex in its anatomy, it presents certain difficulties for surgical tumor removal. 4 Moreover, given the anatomical features of the third ventricle, the clinical presentation of tumors localized there occurs earlier than for tumors inside the lateral ventricles. 25 Among children with such lesions, one of the most common features is the development of hypertensive hydrocephalus.…”
Section: Discussionmentioning
confidence: 99%
“…15,20,27 Gross-total resection has been associated with excellent prognosis, 9,18,20 with 5-year survival being close to 100% after complete resection, but survival is only 56% after subtotal resection. 6,14,15,17,[19][20][21]24,27 Complete initial removal of the tumor is essential to prevent further tumor growth or recurrence, malignant degeneration, 5 continued overproduction of CSF and hydrocephalus, the need for adjuvant therapies such as radiotherapy or chemotherapy, or the morbidity of repeat surgery. …”
Section: Discussionmentioning
confidence: 99%
“…12 In response to this difficulty, endovascular embolization has been advocated as a means to reduce intraoperative blood loss for these tumors. 6,19,20 It has also been suggested that less intraoperative bleeding due to embolization leads to a higher rate of complete resection and better outcome. 11 However, many series have reported a low rate of successful embolization when attempted due to small tortuous vessels that are difficult or impossible to cannulate, or feeding arteries that are judged to also perfuse deep brain structures.…”
Section: B C Kennedy Et Almentioning
confidence: 99%